Assessment of Instructional Resources for Teaching Basic Technology in Junior Secondary Schools in Ogbomoso, Nigeria - Olarinde, L. A.; Fakomogbon, M. A.; Olabisi, A.; Adetunde, I. (IJRDO- Journal of Educational Research, 2017)
This study assessed instructional resources for teaching Basic Technology in Junior Secondary Schoolsin Ogbomoso, Nigeria. Specifically, the study assessed the available non- human resources(workshops, hand tools, machines, audio-visuals and visuals) that are used for teaching BasicTechnology. The researchers also made attempt to find out the functionality of the available resources,it’s frequency of use and their adequacy to the recommendation of NERDC (2007). The researchsample consisted all the 75 junior secondary schools of both private and public schools in Ogbomoso(Ogbomoso South and North, Local Government Areas). The instrument used was a researcherdesignedquestionnaire named ‘Availability and utilization of instructional resources in Teaching BasicTechnology consisting three (3) sections (A, B, & C). The questionnaire was administered, whilefrequency count and percentages were used as statistical method to answer research questions. Theresult of the analysis was as follows: 39 (52.0%) workshops, 60 (5.3%) machines, 310 (9.8%) audiovisuals,1,756 (15.6%) hand tools and 1,422 (63.2%) visuals were available in all the sampled schoolsin Ogbomoso. The data on functionality revealed that 5.2% - 26.7% of the available resources werefunctioning which means that the practical aspects of the subject were thoroughly taken care of. Thefindings also showed that only three (3) out of the twenty-six (26) items used, met the recommendationof the NERDC 2007. Finally, the analyzed results showed that from all the available resources; 26.7% of workshops, 32.3% hand tools, 5% machines, 16.8% audio-visuals and 74% visuals were frequentlyused in the sampled schools.